Mengharmonikan Nilai Ketuhanan dan Tradisi dalam Era Modern - Widya Wulandari; Meyniar Albina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article explains how spiritual values and local traditions can be harmonized in human life in the modern era. The modern era, which is characterized by rapid technological developments, globalization and social change, often presents challenges in preserving spiritual and traditional values. On the one hand, sacred values such as moral and ethical foundations serve as guidelines for individuals and society to maintain a balanced life. On the other hand, local traditions express cultural identity that is rooted in people's lives. This article examines the importance of synergy between the two so that there is no conflict between modernity, religious values and customs. By adopting a dialogical and holistic approach, society can use modernity as a means to strengthen sacred values and maintain the continuity of traditions. This article also describes real examples of communities trying to harmonize the two and offers strategies for achieving harmony between spiritual values and local culture in facing modern-day challenges.